The Effectiveness of Using Youtube Videos in Improving Listening Skills of English Language Education Study Program Students at Wiralodra University Indramayu - Rohdatul Jannah; Didik Himmawan; Nabilah Azzahra; Ainun Fatimatuzzahro (Manajia: Journal of Education and Management, 2025)
The challenge of education in meeting the needs of the internet generation is quite big. This is due to their different life experience of his special experience in using technology. The Internet itself opens up many possibilities for integrating technology into classroom learning. Youtube is one of the learning media that can be integrated with learning subjects that are considered difficult by students. The purpose of this study is to see how far Youtube can be used as a medium of learning in English subjects at Wiralodra University. This study uses a qualitative approach. In the process of collecting data for this study, researchers contacted EFL teachers and EFL students via email to be interviewed in a study interview. The results of the study show that students have a positive perception of using YouTube as a teaching medium in the English language education study program at Wiralodra University, especially in the listening class because the videos they present can be played repeatedly, are easy to use, and easy to access. In addition, they can get so much material for their lectures.